Fabrication of deformable patient-specific AAA models by material casting techniques - Antonuccio, Maria Nicole; Gasparotti, Emanuele; Bardi, Francesco; Monteleone, Angelo; This, Alexandre; Rouet, Laurence; Avril, Stéphane; Celi, Simona (Frontiers in Cardiovascular Medicine, 2023)
Background Abdominal Aortic Aneurysm (AAA) is a balloon-like dilatation that can be lifethreatening if not treated. Fabricating patient-specific AAA models can be beneficial for in-vitro investigations of hemodynamics, as well as for pre-surgical planning and training, testing the effectiveness of different interventions, or developing new surgical procedures.The current direct additive manufacturing techniques cannot simultaneously ensure the flexibility and transparency of models required by some applications. Therefore, casting techniques are presented to overcome these limitations and make the manufactured models suitable for in-vitro hemodynamic investigations, such as particle image velocimetry (PIV) measurements or medical imaging.Methods Two complex patient-specific AAA geometries were considered and the related 3D models were fabricated through material casting. In particular, two casting approaches, i.e. lost molds and lost core casting, were investigated and tested to manufacture the deformable AAA models. The manufactured models were acquired by magnetic resonance, computed tomography (CT), ultrasound imaging, and PIV. In particular, CT scans were segmented to generate a volumetric reconstruction for each manufactured model that was compared to a reference model to assess the accuracy of the manufacturing process.Both lost molds and lost core casting techniques were successful in the manufacturing of the models. The lost molds casting allowed a high-level surface finish in the final 3D model. In this first case, the average signed distance between the manufactured model and the reference was (-0.2 ± 0.2) mm. However, this approach was more expensive and time-consuming. On the other hand, the lost core casting was more affordable and allowed the reuse of the external molds to fabricate multiple copies of the same AAA model. In this second case, the average signed distance between the manufactured model and the reference was (0.1 ± 0.6) mm. However, the final model's surface finish quality was poorer compared to the model obtained by lost molds casting as the sealing of the outer molds was not as firm as the other casting technique.Conclusions Both lost molds and lost core casting techniques can be used for manufacturing 1 Antonuccio et al.patient-specific deformable AAA models suitable for hemodynamic investigations, including medical imaging and PIV.